1976
DOI: 10.1007/bf01973261
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of cyclosporin A: A new antilymphocytic agent

Abstract: The fungus metabolite cyclosporin A is a small peptide acting as a novel antilymphocytic agent. It strongly depressed appearance of both direct and indirect plaque-forming cells and produced a clear dose-dependent inhibition of haemagglutinin formation in mice upon oral administration. Skin graft rejection in mice and graft-versus-host disease in mice and rats were considerably delayed by cycloporin A which also prevented the occurrence of paralysis in rats with experimental allergic encephalomyelitis. This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
253
0
27

Year Published

1982
1982
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,329 publications
(282 citation statements)
references
References 6 publications
2
253
0
27
Order By: Relevance
“…In a previous study we demonstrated with our system the influence of CsA on the secondary antibody response, as well as on the cutaneous immediate and delayed type hypersensitivity reactions to tick salivary antigens (Girardin, Brossard, 1989). This was roughly a consequence of the effects of the drug on the cellular component of the immune system (chiefly the T helper cells) described in detail by others (Borei et al, 1977;Borei, Lafferty, 1983;Thomson et al, 1983a;Thomson et al, 1983b). In another system CsA may also cause perturbations of the development of Schistosoma mansoni through its effects on the immune system of the host (Bueding et al, 1981;Nilsson et al, 1985;Thomson et al, 1986).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In a previous study we demonstrated with our system the influence of CsA on the secondary antibody response, as well as on the cutaneous immediate and delayed type hypersensitivity reactions to tick salivary antigens (Girardin, Brossard, 1989). This was roughly a consequence of the effects of the drug on the cellular component of the immune system (chiefly the T helper cells) described in detail by others (Borei et al, 1977;Borei, Lafferty, 1983;Thomson et al, 1983a;Thomson et al, 1983b). In another system CsA may also cause perturbations of the development of Schistosoma mansoni through its effects on the immune system of the host (Bueding et al, 1981;Nilsson et al, 1985;Thomson et al, 1986).…”
Section: Discussionsupporting
confidence: 60%
“…Cyclosporin A (CsA), an immunosuppressive agent lar gely applied in transplantation surgery, inhibits rejection of allografts (Borei, 1981;Britton, Palacios, 1982), as well as graft versus host reactions (Borei et al, 1977 ;Powles et al, 1980). The properties of this metabolite make it an attractive tool in the investigation of the immune res ponse (Parker et al, 1984;Truffa-Bachi, 1987;Girardin, Brossard, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the iced droplets are lyophilized by a freeze-dryer to prepare composite particles, which are then characterized by fine porous structure producing a large specific surface area; this method is extremely attractive for the development of particles for dry powder inhaler (DPI) because of their specific low density. Therefore, this SFD technique was applied to develop dry powders for inhalation.In this research, ciclosporin, which is currently used as an immunosuppressant for treating a number of autoimmune diseases 15) due to its wide biological activities, including antifungal, anti-inflammatory, and anti-parasitic properties, 16) was used as a model drug. This drug is a macromolecular cyclic peptide and is practically insoluble in water.…”
mentioning
confidence: 99%
“…In 1966, antilymphocyte serum (ALS) and its globulin derivitive (ALG) were introduced as immunosuppressive adjuncts (7). A giant leap forward was made possible by the discovery (8) and then clinical application of Cyclosporin A (9).…”
Section: State Of Art Immunosuppressionmentioning
confidence: 99%